Microwave Induced Stereoselective Conversion of Dialkyl-2-(1,1,3-trioxo-1,3-dihydro-2H-1,2-benzisothiazol-2-yl)- 3-(triphenylphosphoranylidene)succinates to Dialkyl-2-(1,1,3- trioxo-1,3-dihydro-2H-1,2-benzisothiazol-2-yl)-2-butendioates - AHANKAR, HAMIDEH; AMINI, ISSA; RAMAZANI, ALI (Asian Journal of Chemistry, 2010)
Kaolinite powder was found to catalyze conversion of stabilized phosphorus ylides to corresponding electron-poor N-vinylated isothiazoles in solvent-free conditions under microwave irradiation at microwave power 0.6 KW in 3 min in fairly good yields.